The Role of Indonesian Language Lecturers in the Learning Process : (Case Study of Students of Universitas Amal Ilmiah Yapis Wamena) - Hasriani Muslimin (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
This writing aims to provide an understanding of the role of language lecturers in the learning process for students of the Amal Ilmiah YAPIS University in Wamena. Some of the roles of Indonesian language lecturers are as follows: (1) Being a model in using Indonesian both orally and in writing politely in every learning activity with a pattern of educating teaching and training, so that it becomes an example for students in communicating, both in formal and non-formal environments. (2) Creating creative learning and critical thinking both in the field of language and in other fields.